Stability of time-varying switched systems with time-varying delay - Piyapong Niamsup (2018)
In this paper, we investigate the stability of time-varying switched systems with time-varying delay. We first give a generalization of Halanay's inequality and then use this inequality to obtain sufficient conditions for the stability of switched systems. © 2009 Elsevier Ltd. All rights reserved.